2018
DOI: 10.1017/rdc.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

AMS Dates of New Maize Specimens Found in Rock Shelters of the Tehuacan Valley

Abstract: A large collection of maize macro-specimens has been gathered from archaeological sites across the American continent, but only a few have been directly dated by accelerator mass spectrometry (AMS). We recently conducted two new excavations in several rock shelters of Tehuacán valley (San Marcos, Coxcatlán, and Purrón) and uncovered 132 non-manipulated macro-specimens of maize suitable for morphological and paleogenomic analysis, including many complete cobs, stalks, internodes, and leaves. Direct AMS dates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Maize cultivation in SMP has millennial roots: the eldest palaeoecological record stretches back to 6,250 BP in the Guilá-Naquitz Cave, Oaxaca (Benz, 2001;Piperno and Flannery, 2001). Also, ancient vestiges of maize cultivation have been detected throughout SMP: Panama (Piperno et al, 1985), Costa Rica and Nicaragua (Horn, 2016), Salvador (Dull, 2016), Honduras (Kennett et al, 2017), Guatemala (Castanet et al, 2022), Chiapas (Hammond, 2001;Rosenswig et al, 2015), and Puebla (Long and Fritz, 2001;Torres-Rodríguez et al, 2018). The presence of maize in palaeoecological records correlates with human genomic changes, sedentary lifestyle development, and farming techniques (Hünemeier et al, 2012).…”
Section: Maize and The Milpa System The Invention Of Maize And Milpasmentioning
confidence: 99%
“…Maize cultivation in SMP has millennial roots: the eldest palaeoecological record stretches back to 6,250 BP in the Guilá-Naquitz Cave, Oaxaca (Benz, 2001;Piperno and Flannery, 2001). Also, ancient vestiges of maize cultivation have been detected throughout SMP: Panama (Piperno et al, 1985), Costa Rica and Nicaragua (Horn, 2016), Salvador (Dull, 2016), Honduras (Kennett et al, 2017), Guatemala (Castanet et al, 2022), Chiapas (Hammond, 2001;Rosenswig et al, 2015), and Puebla (Long and Fritz, 2001;Torres-Rodríguez et al, 2018). The presence of maize in palaeoecological records correlates with human genomic changes, sedentary lifestyle development, and farming techniques (Hünemeier et al, 2012).…”
Section: Maize and The Milpa System The Invention Of Maize And Milpasmentioning
confidence: 99%
“…1C and SI Appendix , Table S1). Par_N1 is older than any other maize macro-specimen found to date (36).…”
Section: Resultsmentioning
confidence: 80%
“…Importantly, this period saw the first introduction of domesticated maize ( Zea mays ) to the valley and to Coxcatlan Cave in particular. Although MacNeish and the TABP had originally suggested that maize arrived during the Coxcatlan phase, subsequent AMS dating demonstrated that the earliest samples dated to the Abejas phase (Crane and Griffin 1962; Long et al 1989; Torres-Rodríguez et al 2018). After the Abejas phase, Coxcatlan Cave experienced an occupational hiatus for up to 2,500 years, after which time it was reoccupied by people who made and used pottery (Fowler and MacNeish 1972:292).…”
Section: Coxcatlan Cave and The Preceramic Periodmentioning
confidence: 99%
“…The arid conditions of the valley have resulted in the exceptional preservation of organic materials within a series of dry caves, enabling the TABP to recover and document thousands of specimens of early domesticated plants, including chili peppers, avocados, squash, beans, and maize (Long et al 1989; MacNeish 1967b; Mangelsdorf et al 1967; Smith 1967, 2005). Although nearly 200 radiocarbon ages from archaeological settlements across the valley have been produced by the TABP and subsequent projects (Aiuvalasit et al 2010; Johnson and MacNeish 1972; Kaplan and Lynch 1999; Long et al 1989; Neely et al 2015; Smith 2005; Torres-Rodríguez et al 2018), the chronology for the Preceramic phases and the timing of the beginning of plant cultivation within the Tehuacan Valley have remained topics of scrutiny and debate (Fennell 2001; Flannery and MacNeish 1997; Hardy 1996, 1999; MacNeish 1997; Rosenswig 2015:123–125).…”
mentioning
confidence: 99%